Market Failures and Public Intervention: A Vision from the Perspective of the Public Election in Ecuador, Period 2010-2018 - Rizzo-Guambaña, Gabriel (2020)
Diversity of thoughts related to theoretical knowledge and economic political practices; discoveries in the field of economic analysis; the intervention of new technologies; statistics; and, new techniques for monitoring economies, have not succeeded in removing discrepancies; there are now major market failures. The rulers in Ecuador, were and are chosen by sympathy, most voters do not analyze the plan of government that each voter must submit during their candidacy and the beginning of the first year of management. On the other hand, the continuous change of ideologies, initiating when the state should not intervene in the market assuming that things would improve on their own (Neoliberal politics); and then, when the state decides to intervene in the market, creating an artificial economy (neo-Keynesian politics). This study was based on documentary-based analytical research, using inductive, analytical and synthesis research methods. Concluding that there is no defined policy in Ecuador, which we would say applies to it as appropriate as the nominated authorities.